2008
DOI: 10.1002/adma.200701102
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Wrapped Single‐Walled Carbon Nanotube Hybrid Fibers for supercapacitors and Artificial Muscles

Abstract: Multifunctional carbon nanotube (CNT) composite fibers are currently of considerable interest in applications where actuation and energy-storage functions are highly desirable, such as electronic textiles. CNT fibers have been shown to function as excellent electrochemical supercapacitors giving specific capacitances of 100 F g -1 [1] . CNT assemblies can also produce useful actuation strains when electrochemically charged [2] and can potentially operate to high stresses because of the excellent mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
49
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 22 publications
(33 reference statements)
1
49
0
Order By: Relevance
“…Because of the sp 2 carbon atoms in the polycyclic aromatic hydrocarbon chemistry of the graphene tubes in CNTs and the exclusive Schiff's base glutaraldehyde crosslinking reaction of GOx-BSA proteins, covalent interactions between CNTs and GOx-BSA layers are not feasible. Hence, the GOx layer is expected to interact with CNT fiber non-covalently, which is consistent with reports that different enzymes, polypeptides and DNA can interact non-covalently with CNT [28][29][30][31][32][33][34][35]. The interactions between proteins and CNT are reported to involve many types of non-covalent forces, including electrostatic, hydrogen bonding, hydrophobic and π-π interactions; and strong non-covalent interactions were also demonstrated between GOx and DWNTs [34].…”
Section: The Cnt Fiber Electrodesupporting
confidence: 87%
“…Because of the sp 2 carbon atoms in the polycyclic aromatic hydrocarbon chemistry of the graphene tubes in CNTs and the exclusive Schiff's base glutaraldehyde crosslinking reaction of GOx-BSA proteins, covalent interactions between CNTs and GOx-BSA layers are not feasible. Hence, the GOx layer is expected to interact with CNT fiber non-covalently, which is consistent with reports that different enzymes, polypeptides and DNA can interact non-covalently with CNT [28][29][30][31][32][33][34][35]. The interactions between proteins and CNT are reported to involve many types of non-covalent forces, including electrostatic, hydrogen bonding, hydrophobic and π-π interactions; and strong non-covalent interactions were also demonstrated between GOx and DWNTs [34].…”
Section: The Cnt Fiber Electrodesupporting
confidence: 87%
“…The electrical conductivity of the dried hybrid film was 24 ± 1.8 S/cm as measured by a four-point probe method. [27] . Even after drying (films containing ~47% GelMA/DNA which was confirmed by thermogravimetric analysis (TGA), Figure S2 ), the conductivity of these films was higher than 2D printed graphene patterns (0.1 – 100 S/m).…”
mentioning
confidence: 99%
“…The enhanced mechanical stability of the ink might be due to the strong the π–π and hydrophobic interactions between the GelMA/DNA chains and MWCNTs sidewalls. [27] …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Several studies are particularly devoted to the generation of SWCNT-DNA nanoarchitectures via noncovalent interaction for multiple application include electronics, biomedical, and were reviewed elsewhere. [19] Shim et al reported the mechanical strength of PVA polymer can be improved by incorporation of CNTs. [1] Besides, incorporation of POSS into resins gives rise in tensile strength and mechanical properties, and can 346 R. SUBBIAH ET AL.…”
Section: Introductionmentioning
confidence: 99%